Implementasi Sistem Penunjang Keputusan Untuk Menentukan Kelayakan Kendaraan Pada Perusahaan Ekspedisi Dengan Pendekatan Saw Dan Fuzzy Logic : (Studi Kasus: Pt. Bangun Perkasa Ekspress) - Fadly Ariadi; Yohannes Agustin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
This study aims to develop and implement a decision support system using the Simple Additive Weighting (SAW) and Fuzzy Logic methods to assess vehicle feasibility in expedition companies, with a case study at PT. Bangun Perkasa Ekspress. Vehicle feasibility is a critical aspect of the logistics industry, directly impacting safety, operational efficiency, and company costs. However, manual evaluation processes often lead to subjective and suboptimal decisions. Therefore, the decision support system is designed to objectively evaluate vehicle feasibility by considering various critical criteria, such as engine condition, vehicle age, and maintenance history. This research employs the SAW method to assign weights and quantitative assessments to criteria, while the Fuzzy Logic method manages data uncertainty. Implementation results indicate that the system effectively improves operational efficiency by speeding up the evaluation process, enhancing decision accuracy, and reducing accident risks and maintenance costs. Thus, this decision support system significantly contributes to improving operational performance and competitive advantage in the logistics industry.